2014
DOI: 10.1089/apc.2013.0262
|View full text |Cite
|
Sign up to set email alerts
|

“Payment by Results”—Financial Incentives and Motivational Interviewing, Adherence Interventions in Young Adults with Perinatally Acquired HIV-1 Infection: A Pilot Program

Abstract: Emerging evidence suggests financial incentives (FIs) improve medication adherence in select populations. A small proportion of adolescents with perinatal HIV (PaHIV) transfer to adult services with established poor adherence and advanced disease. We describe a single center adherence intervention combining FIs with motivational interviewing (MI). Eligible patients (PaHIV,16-25 years, CD4 count ≤ 200, off ART despite multiple attempts) received MI, and FI dependent on viral load (VL) reduction for 1 year. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 20 publications
1
64
0
Order By: Relevance
“…Early pilot studies have shown encouraging outcomes for motivational interviewing in reducing viral load and unprotected sex and warrant well powered, age stratified randomized controlled trials. [19][20][21] Practical reasons such as holidays or being busy with other activities were frequently identified as a barrier to adherence, and medication-related factors such as once daily regimens and smaller pill sizes were most commonly identified as factors that may improve adherence. Both factors are related to the convenience of taking the medication and suggest efforts to ease medication at a younger age, whilst adherence is still maintained, such as simplification to once daily regimens and FDCs may prove to be beneficial and are welcomed by adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Early pilot studies have shown encouraging outcomes for motivational interviewing in reducing viral load and unprotected sex and warrant well powered, age stratified randomized controlled trials. [19][20][21] Practical reasons such as holidays or being busy with other activities were frequently identified as a barrier to adherence, and medication-related factors such as once daily regimens and smaller pill sizes were most commonly identified as factors that may improve adherence. Both factors are related to the convenience of taking the medication and suggest efforts to ease medication at a younger age, whilst adherence is still maintained, such as simplification to once daily regimens and FDCs may prove to be beneficial and are welcomed by adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…66,68,69 Fortunately, intervention researchers have started to demonstrate the feasibility of incorporating motivational interviewing and cognitivebehavioral interventions into integrated HIV youth treatment settings. 36,[63][64][65][66] However, much work is still needed in the development of such interventions to best serve the psychosocial and medical needs of young African American males living with HIV.…”
Section: Limitationsmentioning
confidence: 99%
“…34 In addition, recent pilot studies with YLH have evaluated novel interventions such as cell phone support 35 as well as utilizing motivational interviewing techniques and financial incentives to increase ART adherence. 36 To date, such studies have shown promise for improving ART adherence among YLH. However, limitations of the aforementioned studies include small sample sizes as well as significant variability among samples (e.g., behavioral vs. perinatal acquisition; disparate sociodemographics and adherence methodology), which notably limits our understanding of predictors and pathways of ART adherence outcomes for young African American males living with HIV.…”
mentioning
confidence: 99%
“…This may suggest that incentives play an important role in helping nonadherent youth stick to their medication. 15 There have been limited data published on the acceptability of adherence interventions with HIV + youth. A small pilot study (N = 18) found 61% preferred motivational interviews to regular office visits.…”
Section: Introductionmentioning
confidence: 99%